Mini-HA Is Superior to Full Length Hemagglutinin Immunization in Inducing Stem-Specific Antibodies and Protection Against Group 1 Influenza Virus Challenges in Mice - van der Lubbe, Joan E. M.; Verspuij, Johan W. A.; Huizingh, Jeroen; Schmit-Tillemans, Sonja P. R.; Tolboom, Jeroen T. B. M.; Dekking, Liesbeth E. H. A.; Kwaks, Ted; Brandenburg, Börries; Meijberg, Wim; Zahn, Roland C.; Roozendaal, Ramon; Kuipers, Harmjan (Frontiers in Immunology, 2018)
Seasonal influenza vaccines are updated almost annually to match the antigenic drift in influenza hemagglutinin (HA) surface glycoprotein. A new HA stem-based antigen, the so-called “mini-HA”, was recently shown to induce cross-protective antibodies. However, cross-reactive antibodies targeting the HA stem can also be found in mice and humans after administration of seasonal vaccine. This has raised the question whether in similar conditions such a mini-HA would be able to show an increased breath of protection over immunization with full length (FL) HA. We show in mice that in a direct comparison to H1 FL HA, using the same immunization regimen, dosing and adjuvant, a group 1 mini-HA has a higher protective efficacy against group 1 influenza virus challenges not homologous to the H1 FL HA. Although both antigens induce a similar breadth of HA subtype binding, mini-HA immunization induces significantly more HA stem-specific antibodies correlating with survival. In addition, both mini-HA and H1 FL HA immunization induce influenza neutralizing antibodies while mini-HA induces significantly higher levels of mFcγRIII activation, involved in Fc-mediated antibody effector functions. In agreement with previous findings, this confirms that more than one mechanism contributes to protection against influenza. Together our results further warrant the development of a universal influenza vaccine based on the HA stem region.